¿Cuál es el alcance de las facultades del juez en lo atinente a la adquisición, producción y valoración de la prueba en el proceso penal de la provincia de Buenos Aires? - Giuliani, Gabriel (2018)
According to our constitutional law (article 18) the legal process in court covers not only the right to prove the information that shows whether something is a fact or not; but also the right to have a fair hearing (article 14.1 International Covenant on Civil and Political Rights) . The prosecuting lawyer and the defendant must try to prove the facts with evidence that will support their claims by all possible and legal means. And the judge who leads the trial will decide on the sentence with freedom and imparciality. In this research, we pretend to prove that the judge´s imparciality has been put at risk in Buenos Aires State since 1998, when the law that regulate the trial, was reformed.